Manufacturing excellence for 21st century production - Hitomi, Katsundo
A new concept, 'Manufacturing excellence', is presented to enhance the suitability of tangible goods production for pursuing human happiness and world peace, whilst eliminating the earth destructive activity caused by conventional mass production, mass consumption and mass disposal which wastes enormous amounts of valuable natural resources. Several approaches to manufacturing excellence-CIM-led factory automation, human-centered flexible manufacture, production for customer satisfaction, green production for environmental elegance, high added-value production, etc. - are discussed. Finally, socially appropriate manufacturing is proposed as a production perspective for the 21st century.
The writer is concerned with the radical changes which must take place to achieve manufacturing excellence and discusses several approaches : socially appropriate manufacturing is proposed as a production perspective.
Keywords: Manufacturing excellence; Production